Using Clustering Techniques to Plan Indoor Femtocell Base Stations Layout in Multi-floors. (7th March 2019) - Ibrahim, Lamiaa F; Salman, Hesham A; Sery, Sara Y; Taha, Zaki
Abstract: Long-term evolution 'LTE' advanced-based heterogeneous networks are used to improve spectral efficiency per unit area. Nowadays, the network specialists try to increase the capacity of indoor by adding indoor base stations, but other problems appear to them because they are adding them without considering critical constraints such as the number of users, type of base stations, and type of wall, indoor and outdoor interference. This paper proposed a system using cluster techniques to facilitate the process of cell planning that involves locating and configuring infrastructure for mobile networks. The density-based spatial clustering of applications with noise (DBSCAN) algorithm was modified to solve the problem of coverage indoor area, with the existence of obstacles to choose suitable femtocell stations which satisfy minimum path loss and maximize coverage area and minimize cost with guaranteed path loss threshold. Subsequently, Hierarchical Agglomerative Clustering (HAC) was modified to maximize Signal to Interference plus Noise Ratio SINR. Suitable penetrations of 4 and 5 G are used and different types of obstacles taking into consideration their penetration values. The results of this algorithm indicate that the proposed algorithm conducts to decrease the number of Femtocells so minimize the cost and maximize SINR with a grantee pass loss threshold.